HUBUNGAN INTERAKSI TEMAN SEBAYA DENGAN PERILAKU MEROKOK PADA ANAK REMAJA DI SMP NEGERI 3 SIEMPAT NEMPU HULU SIDIKALANG - Nella Cintya Pandiangan; Dior Manta Tambunan (Indonesian Trust Nursing Journal, 2026)
Adolescents are an age group in a transitional phase toward adulthood and are highly susceptible to environmental influences, especially from peers. Peer interaction can shape both positive and negative behaviors, including smoking behavior. Smoking among adolescents is a serious health problem because it can lead to nicotine dependence and increase the risk of chronic diseases from a young age. The objective of this study is to determine the relationship between peer interaction and smoking behavior among adolescents at SMP Negeri 3 Siempat Nempu Hulu, Sidikalang.This study employed a quantitative approach with a cross-sectional study design. The sampling technique used was total sampling, involving 51 respondents. Data were collected using questionnaires on peer interaction and smoking behavior. Data analysis was performed using the Spearman Rank correlation test. The results showed a significant relationship between peer interaction and smoking behavior among adolescents, with a p-value <0.05 and a correlation coefficient of r = –0.576. This indicates that the stronger the positive peer interaction, the lower the tendency of adolescents to engage in smoking behavior.There is a significant relationship between peer interaction and smoking behavior among adolescents. Future researchers are expected to include additional variables such as parental supervision, family support, and the effect of social media.